2019
DOI: 10.32615/ps.2019.060
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance and sugar variations during key reproductive stages of soybean under potassium iodide-simulated terminal drought

Abstract: Importance of utilizing chemical desiccants to simulate terminal drought effects is gradually increasing. In the present study, a potassium iodide (KI)-simulated terminal drought stress was imposed during the full bloom (R2), pod elongation (R4), and seed initiation (R5) stages of soybean; the KI-induced desiccation effects were assessed at 1, 3, and 5 d after spraying (DASP). Plants responded to KI-simulated terminal drought stress within 1 DASP of KI-treatment, in terms of photosynthetic and transpiration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Additionally, simple sugars and total nonstructural leaf carbohydrates were higher at beginning and full pod (R3/R4) compared to the earlier soybean growth stages (Rogers et al, 2004). Sengupta et al (2019) also reported an increase in hexose and sucrose concentrations in R5 compared to the R2 leaves, but in drought‐stressed soybean plants.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, simple sugars and total nonstructural leaf carbohydrates were higher at beginning and full pod (R3/R4) compared to the earlier soybean growth stages (Rogers et al, 2004). Sengupta et al (2019) also reported an increase in hexose and sucrose concentrations in R5 compared to the R2 leaves, but in drought‐stressed soybean plants.…”
Section: Discussionmentioning
confidence: 94%
“…The PPFD on cuvette was provided by a LED external source (A113, Qubit System) which supplies photosynthetically active radiation to the leaf with minimum heat load. Net photosynthesis ( A N ), transpiration ( E ), and stomatal conductance to vapor ( g s ) were calculated according to the LoggerPro software (Qubit Systems Inc., Canada) as reported in Sengupta et al 2019 .…”
Section: Methodsmentioning
confidence: 99%
“…The PPFD on cuvette was provided by a LED external source (A113, Qubit System) which supplies photosynthetically active radiation to the leaf with minimum heat load. Net photosynthesis (A N ), transpiration (E), and stomatal conductance to vapor (g s ) were calculated according to the LoggerPro software (Qubit Systems Inc., Canada) as reported in Sengupta et al 2019. Using the differential CO 2 concentration, which is the difference between the influx and efflux CO 2 (dif. CO 2 ), following the molecular flow (MF) rate, net-photosynthesis was calculated as follows:…”
Section: Gas Exchange Analysismentioning
confidence: 99%